Cell-cell and cell-matrix adhesion regulated by Piezo1 is critical for stiffness-dependent DRG neuron aggregation - Mengshi Lei; Weiyou Wang; Hong Zhang; Jihong Gong; Zhili Wang; Hanmian Cai; Xiaofei Yang; Shen Wang; Cong Ma (Cell Reports, 2023)
Summary: The dorsal root ganglion (DRG) is characterized by the dense clustering of primary sensory neuron bodies, with their axons extending to target tissues for sensory perception. The close physical proximity of DRG neurons facilitates the integration and amplification of somatosensation, ensuring normal physiological functioning. However, the mechanism underlying DRG neuron aggregation was unclear. In our study, we culture DRG neurons from newborn rats on substrates with varying stiffness and observe that the aggregation of DRG neurons is influenced by mechanical signals arising from substrate stiffness. Moreover, we identify Piezo1 as the mechanosensor responsible for DRG neurons’ ability to sense different substrate stiffness. We further demonstrate that the Piezo1-calpain-integrin-β1/E-cadherin signaling cascade regulates the aggregation of DRG neurons. These findings deepen our understanding of the mechanisms involved in histogenesis and potential disease development, as mechanical signals arising from substrate stiffness play a crucial role in these processes.